2018
DOI: 10.1371/journal.pmed.1002691
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to identify pairwise interactions between specific IgE antibodies and their association with asthma: A cross-sectional analysis within a population-based birth cohort

Abstract: BackgroundThe relationship between allergic sensitisation and asthma is complex; the data about the strength of this association are conflicting. We propose that the discrepancies arise in part because allergic sensitisation may not be a single entity (as considered conventionally) but a collection of several different classes of sensitisation. We hypothesise that pairings between immunoglobulin E (IgE) antibodies to individual allergenic molecules (components), rather than IgE responses to ‘informative’ molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
109
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 42 publications
10
109
1
2
Order By: Relevance
“…In most studies of allergen control (and in clinical practice), individuals are assigned as either sensitized or not based on arbitrary cut-off points on skin tests or measurement of specific serum IgE. However, a sizeable proportion of such defined "atopic" individuals have no evidence of symptoms upon exposure, and it has been suggested that sensitization may include several different subtypes (benign and pathologic (67)), which differ in their association with asthma(68,69).…”
mentioning
confidence: 99%
“…In most studies of allergen control (and in clinical practice), individuals are assigned as either sensitized or not based on arbitrary cut-off points on skin tests or measurement of specific serum IgE. However, a sizeable proportion of such defined "atopic" individuals have no evidence of symptoms upon exposure, and it has been suggested that sensitization may include several different subtypes (benign and pathologic (67)), which differ in their association with asthma(68,69).…”
mentioning
confidence: 99%
“…(2018), які вивчали специфічні IgE у сироватці крові на 112 алергенних компонентах найбільш сучасним методом мультиплексної матриці ImmunoCAP у когорті дітей віком 11 років (n = 461). Методами кластеризації, логістичної регресії виявлено 18 алергенних компонентів, що з доведеними високими чутливістю (0,84) та специфічністю (0,87) є значущими при формуванні імунопатологічної відповіді [11].…”
Section: обговоренняunclassified
“…as well as to previously machine learning-derived allergy clusters [290][291][292][293] , to assess involvement in allergy development. Subsequently, possible predictive and longitudinal effects on allergy outcomes of the circulating chemokine levels were investigated using logistic regression and generalised estimating equation (GEE) models.…”
Section: Paper I -Chemokine Studies In the Manchester Asthma And Allementioning
confidence: 99%